A decade together - UMP and HsKA strengthen cooperation in German Engineering program - Siti Nur Azwin, Zulkapri (2020)
Pekan, 14 July 2020 - The ten years of collaboration networking between Universiti Malaysia Pahang (UMP) and the Karlsruhe University of Applied Sciences (HsKA), which is among the best universities in Germany, has developed a model of German engineering education, the Fachhochschule, to be adopted into the education system in this country.